Marginal contributions and externalities in the value - Geoffroy De Clippel; Roberto Serrano (Brown University, Department of Economics, 2005)
Our concern is the extension of the theory of the Shapley value to problems involving externalities. Using the standard axiom systems behind the Shapley value for an arbitrary exogenous coalition structure leads to the identification of bounds on players' payoffs around an “externality-free” value. In endogenizing the coalition structure, we analyze a two-stage process of coalition formation in whose second stage our axiomatic results are applied. We find reasons to explain inefficient coalition structures, and provide sufficient conditions for efficiency. – externalities ; marginal contributions ; Shapley value ; Pigouvian transfers ; coalition formation
Keywords: C7; D62; 330; Spieltheorie; Shapley-Wert; Externer Effekt; Koalition; Theorie